Keberkesanan Program Pusat Islamdalam Membentuk Sahsiah Pelajar : KajianPerbandingan Antara UPSI dan UKM: The Effectiveness of The Programs in Islamic Centresin Moulding Students’ Characters: A ComparativeStudy Between UPSI and UKM - Abd Ghani, Abd Rahman (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2014)
Good character is a very important asset to a student. A student’s success is not only measured by his knowledge, but also in terms of his character. Apart from the role of played by the institution of higher learning(IHL) itself, Islamic centres in an IHL are also actually very instrumental in shaping the personality of students, because a lot of programs conducted are tailored towards this aim. This study examines the extent of the roles played by the Islamic centers of two IHLs namelyUniversiti Pendidikan Sultan Idris (UPSI) Universiti Kebangsaan Malaysia (UKM) in realizing that goal. This study is qualitative and quantitative in approach, utilizing explotary method involving library research and field research. This study uses questionnaires and comparative analysis in order to make the comparison. The main objective of this study is to examine the effectiveness of the religious and social programs conducted by the Islamic centers of UPSI and UKM. Sampling involved 100 respondents, 50 from UPSI students and 50 from UKM. Data were analyzed using Statistical Packages for Social Sciences (SPSS) version 17.0 using the Likert scale for frequencies, percentages and means. The overall results showed some differences of effectiveness between the approaches used by the Islamic Centerof UPSI as compared to the Islamic Center of UKM.